3D concrete printing technology: enhancing productivity in the South African construction industry – exploring the benefits, barriers, and improvement strategies - Mogale, Setekoane Phillemon (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.